A conspectus of the silver-flies (Diptera: Chamaemyiidae) of the Middle East with descriptions of new species of Chamaemyia Meigen and Melanochthiphila Frey, from the Arabian Peninsula - Ebejer, M.j. (Zootaxa, 2017)
An overview of the Chamaemyiidae of the Middle East is given with species distribution within the Arabian Peninsula. For countries bordering Saudi Arabia, the distribution is tabulated. Data on new records for species of Chamaemyiidae from countries within the Arabian Peninsula are included. Descriptions and illustrations are provided for Chamaemyia aurilinea sp. n., C. grisea sp. n., C. xanthopoda sp. n. and Melanochthiphila arabica sp. n. from Saudi Arabia.